Association of anemia and SRH in older people: the SONIC study. Issue 7 (8th June 2020) - Noma, Tomoko; Kabayama, Mai; Gondo, Yasuyuki; Yasumoto, Saori; Masui, Yukie; Sugimoto, Ken; Akasaka, Hiroshi; Godai, Kayo; Higuchi, Atsuko; Akagi, Yuya; Takami, Yoichi; Takeya, Yasushi; et al.
Abstract : Aim: The incidence of anemia increases with aging, and it is considered to affect mortality through complex pathophysiological outcomes. Although it has been suggested that self‐rated health may also contribute to the prognosis of anemia in older people, the relationship between anemia and self‐rated health is not well understood. This study thus examined the actual status of anemia in older community‐dwelling Japanese people and clarified the relationship between anemia and self‐rated health. Methods: We conducted medical interviews, physical measurements and blood testing in 2083 people aged 69–91 years who participated in the long‐term observational Septuagenarians, Octogenarians, Nonagenarians, Investigation with Centenarians (SONIC) study. Subjects were divided into two groups according to whether they had anemia. Logistic regression analyses were used to assess the relationship between anemia and self‐rated health after adjusting for possible confounding factors. Results: The prevalence of anemia was 22.3% in all participants, 7.2% in men and 11.6% in women aged 69–71 years, 27.4% in men and 26.3% in women aged 79–81 years, and 55.8% in men and 44.9% in women aged 89–91 years. Multivariate analysis revealed a correlation between the presence of anemia and poor self‐rated health in all (odds ratio 0.67, 95% confidence interval 0.48–0.93) and aged 69–71 years (odds ratio 0.47, 95% confidence interval 0.25–0.86). Conclusions: Anemia was associated with self‐rated health in older Japanese people, suggesting that careful management of anemia may contribute to health and longevity. Geriatr Gerontol Int 2020; : – .